2012
DOI: 10.1353/eca.2012.0018
|View full text |Cite
|
Sign up to set email alerts
|

The Ins and Outs of Forecasting Unemployment: Using Labor Force Flows to Forecast the Labor Market

Abstract: This paper presents a forecasting model of unemployment based on labor force flows data that, in real time, dramatically outperforms the Survey of Professional Forecasters, historical forecasts from the Federal Reserve Board's Greenbook, and basic time-series models. Our model's forecast has a root-mean-squared error about 30 percent below that of the next-best forecast in the near term and performs especially well surrounding large recessions and cyclical turning points. Further, because our model uses inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 44 publications
1
77
0
1
Order By: Relevance
“…8 For the estimation of univariate models, ARIMA(2,0,1) and ARIMA(2,1,0), I used rolling regression with a fixed window only. Following Barnichon and Nekarda (2012), I also compute the forecasts using their nonlinear steady-state model with constant hazards (s t and f t ), which does not require rolling regression of any type.…”
Section: Estimation and Forecasting Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…8 For the estimation of univariate models, ARIMA(2,0,1) and ARIMA(2,1,0), I used rolling regression with a fixed window only. Following Barnichon and Nekarda (2012), I also compute the forecasts using their nonlinear steady-state model with constant hazards (s t and f t ), which does not require rolling regression of any type.…”
Section: Estimation and Forecasting Methodsmentioning
confidence: 99%
“…random variables with mean 0 and variance and ARIMA(2,1,0) as univariate forecasting models, the two specifications commonly used in the literature (Montgomery et al 1998;Barnichon and Nekarda, 2012).…”
Section: Alternative Forecasting Models Univariate Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed study regarding unemployment forecasts and predictions performance carried out by Barnichon and Nekarda (2012) Heilemann and Stekler (2013) offered several reasons for the lack of accuracy of G7 predictions in the last 50 years. They identified one continuous critique brought to macro-econometric models and forecasting techniques, but also concluded that the accuracy expectations are not realistic.…”
Section: Literaturementioning
confidence: 99%